British Theatre Archives: Scattered but Accessible - D’Ambrosio, Amber (Qualitative and Quantitative Methods in Libraries, 2017)
Theatres are often under-funded, yet they produce a vast amount of archival material that is not limited to documents.  The archival material produced by a theatre has immediate value to future performances, whether through the re-use of costumes and props, or through the analysis of stage directions and/or video recordings of previous performances. The trend in digitizing archival and special collections materials provides new opportunities for access to finding aids and collections. However, most theatre archives cannot afford to provide this level of access to their collections or even the traditional option of in person research opportunities. The focus of this study is to examine the archives of selected British theatres, theatre companies and educational/cultural organizations to determine how the archives are managed, how collections differ based on the type of institution in which they are housed, and access to the collections. Unlike existing work on theatre archives, this research looks critically at the various manifestations of archives related to theatre and how the type of institution maintaining a collection affects its completeness, organization and accessibility.